The Oxford Book of Military Anecdotes - Edited By Hastings, Max (GHQ, Rawalpindi Army Education, 1989)
The collection is principally British and American, with `occasional forays among the ranks of foreign armies'.
Include Index
Keywords: Military art and science -- Military history -- Soldiers